Hospital mattresses: Thermal disinfection against bacteria, fungi and virus - Maschio-Lima, Taiza; Pacca, Carolina Colombelli; Almeida, Bianca Gottardo de; Byzynski, Gabriela; Almeida, Margarete Teresa Gottardo de (Brazilian Journal of Case Reports, 2023)
Disinfection protocols for medical items play an important role in the prevention and con-trol of healthcare-associated infections. Regarding mattresses, disinfection with chemical products only cleans the surface, leading to failures in the execution of final processes of cleaning. This study aims to evaluate the antimicrobial activity of ECOSTOVE Thermal Chamber for the disinfection of hospital mattresses. Microbiological analyses were carried out under different experimental con-ditions, considering microbial viability, treatment time and position of inoculum on mattress. Staphylococcus aureus, Klebsiella pneumoniae, Candida albicans and Chikungunya virus were in-oculated at five pre-defined positions on the external and internal areas of hospital mattresses. Im-prints were done using RODAC plates, before and after heat treatment to evaluate colony-forming unit and microbial viability. The percentage of microbial inhibition obtained by heat treatment of the ECOSTOVE varied between 83.1 to 100%. The best results were observed for the enveloped Chikungunya (100% inhibition) and C. albicans (between 97.6 and 100%), followed by K. pneu-moniae (85.4-100%) and S. aureus (83.1-99.1%). Due to the significant antimicrobial activity of ECOSTOVE, it can be integrated into standard hospital hygiene and cleaning procedures as a prom-ising strategy in the control of healthcare-associated infections.